ANALISIS KINERJA KEUANGAN BANK SEBELUM DAN SESUDAH DIAKUISISI - Munaf, Tommy; Mahfuddin, Rohmat (STIE PEMBANGUNAN TANJUNGPINANG, 2022)
The purpose of this research is to find out whether there has been an improvement in the financial performance of Bank Permata after it was acquired by comparing the financial performance of the banks two years before and two years after. This study uses financial ratio analysis of LDR, CAR, ROA, BOPO, NPL as the calculation. The method used in this study is a qualitative method using secondary data. The object of this research is Permata Bank. Data collection was carried out by means of literature studies and documentation. Where data is obtained from Bank Permata's financial reports. Based on the results of the financial performance analysis at Permata Bank, it was concluded that LDR, CAR, NPL had improvements in Permata Bank's financial performance. Meanwhile, ROA and BOPO did not improve after being acquired but are in a safe position for the soundness of the bank